Spray-Drying Encapsulation of the Live Biotherapeutic Candidate Akkermansia muciniphila DSM 22959 to Survive Aerobic Storage - Joana Cristina Barbosa; Diana Almeida; Daniela Machado; Sérgio Sousa; Ana Cristina Freitas; José Carlos Andrade; Ana Maria Gomes (Pharmaceuticals, 2022)
Akkermansia muciniphila is regarded as a promising next-generation probiotic or live biotherapeutic candidate. Effective delivery strategies must be developed to ensure high enough viability of the probiotic strain throughout its industrial formulation, distribution chain, shelf-life, and, ultimately, the host’s gastrointestinal tract, where it should exert its beneficial effect(s). Among the possible methodologies, spray-drying is considered industrially attractive regarding its costs, efficiency, and scalability, with the due parameter customization. In this study, spray-drying was explored as a one-step process to encapsulate A. muciniphila DSM 22959, testing the drying settings and three different dairy-based matrices. Microcapsule morphology and size was assessed, and viability throughout storage at 4 or 22 °C and simulated gastrointestinal passage was determined. Akkermansia muciniphila microencapsulation by spray-drying, using 10% skim milk and inlet/outlet temperatures of 150/65 °C, is effective in terms of viability stabilization, both during prolonged aerobic storage and exposure to simulated gastrointestinal passage. Akkermansia muciniphila viability was maintained at around 107 CFU/g up to 28 days at 4 °C under aerobic conditions with viability losses inferior to 1 log reduction. This methodology provides the necessary conditions to efficiently deliver the recommended dose of live A. muciniphila in the human gut as a live biotherapeutic product.